Luther und die Folgen für die Kunst: Hamburger Kunsthalle [11. November 1983 - 8. Januar 1984] - Hofmann, Werner; Dierker, Martin Johannes; Beutler, Christian; Huber, Martin; Luther, Martin (Prestel-Verl., 1983)
Zahlr. Darst. zu Luthers Leben